Design of Porous Asphalt Pavement for Storm Water Management - Kumar, Sanjeev (My University, 2019)
Water is most important substance on earth for sustaining life. At present, one third of the world population is facing water scarcity and the situation is going to worsen in the future. At present depletion rate, it is estimated that this number can grow upto two third of the world population in the coming future, unless we come up with the some indigeneous water conservation techniques and technologies. One such technology is porous asphalt pavement, which can help in achieving effective strong water management. The design of the porous asphalt pavement differ from the regular pavement. The Porous Asphalt Pavement has porous structure which allows water to percolate through the pavement into the soil, thus recharging the ground water table. Asphalt Pavement has many advantages like reducing the amount of surface runoff, noise reduction, skid improvement on the surface of the pavement and improving surface reflectivity etc, so this technology can not only help in water conservation but can also be beneficial in improving the performance and safety characteristics of the road. The important feature which enables the asphalt pavement to exhibit a porous nature is the increase air void content. Air void content of the asphalt mix is the key parameter which determines the design and performance of the porous asphalt pavement. The objective of this study is to come up with an effective design for three layers of porous asphalt pavement named as viz. surface layer, filter layer / choker layer and reservoir layer. Surface layer is designed using Marshall Mix design methodology, considering Indian climatic condition. Performance testing including drain-down susceptibility, cantabro susceptibility, moisture induced damage susceptibility, indirect tensile strength testing, dynamic creep testing, skid measurement and permeability testing will be conducted in this study to design porous asphalt pavement.
ME Thesis
Keywords: Porous Asphalt Pavement; Hydraulic Design; Skid Resistance